2007
DOI: 10.1071/wr06052
|View full text |Cite
|
Sign up to set email alerts
|

Resource selection by grazing herbivores on post-fire regrowth in a West African woodland savanna

Abstract: The preference of grazing herbivores to feed on grass regrowth following savanna fires rather than on unburnt grass swards is widely recognised. However, there is little information on which factors govern patterns of resource selection within burnt areas. In this study, we attempted to disentangle the effects of different habitat and grass sward characteristics on the utilisation of post-fire regrowth by nine species of ungulates in a fire-dominated woodland savanna in north Cameroon. We used resource-selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 25 publications
(27 reference statements)
5
47
0
1
Order By: Relevance
“…The high overlap does not necessarily also imply nutritional overlap since different herbivore species can select post-fire regrowth of different age (Klop et al 2007) and hence, different nutritional quality (Van de Vijver et al 1999). Although our study provides insight into the importance of body mass, diet quality and diet composition on patterns of resource partitioning among West African herbivores in the dry season and early wet season, further research is needed to investigate patterns of resource partitioning deeper into the wet season, when many herbivores graze on the grazing lawns of hippopotamus (Verweij et al 2006) instead of the postfire regrowth that is abundant in the dry season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high overlap does not necessarily also imply nutritional overlap since different herbivore species can select post-fire regrowth of different age (Klop et al 2007) and hence, different nutritional quality (Van de Vijver et al 1999). Although our study provides insight into the importance of body mass, diet quality and diet composition on patterns of resource partitioning among West African herbivores in the dry season and early wet season, further research is needed to investigate patterns of resource partitioning deeper into the wet season, when many herbivores graze on the grazing lawns of hippopotamus (Verweij et al 2006) instead of the postfire regrowth that is abundant in the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not specifically test this hypothesis, the generally low animal densities, the seemingly abundant supply of grass and the good physical condition (estimated visually) of herbivores even at the end of the dry season showed no apparent indication of limited resources. In addition, herbivore species in Bénoué NP have been shown to differ in patterns of habitat use and spatial distribution in the burned landscape during the dry season (Klop et al 2007, Mayaka 2002. In this respect it is interesting that Namgail (2009) and Namgail et al (2004) demonstrated that blue sheep (Pseudois nayaur) in assemblage with one additional sympatric species, the Ladakh urial (Ovis vignei vignei), showed larger niche width and more niche overlap with abundant food resources, compared with a situation with less abundant food resources and two additional sympatric species, feeding on the same resource.…”
Section: Diet Selection and Resource Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…As we measured most environmental factors at a scale finer than that of time since fire (i.e., environmental factors are nested within fire patches), individual animals were nested within fire patch as a random intercept (Gillies et al 2006). We created models using various combinations of environmental factors; as the influence of time since fire is likely to be highly influential (Vinton et al 1993;Fuhlendorf and Engle 2004;Archibald et al 2005;Klop et al 2007), we included interaction terms for this variable with all others individually (i.e., time since fire and distance to water, time since fire and slope, etc.). In all models with interaction terms, main effects of both variables were included.…”
Section: Methodsmentioning
confidence: 99%
“…Fires may alter the distribution of herbivore species because of a change in resource availability , Moe et al 1990). In addition, patterns of resource selection by different ungulates may be governed largely by spatial variation in the quality and structure of the burned grass sward (Klop et al 2007). Finally, species may show differential preference for this post-fire regrowth because of differences in diet (Gureja & Owen-Smith 2002, Tomor & Owen-Smith 2002 or body mass (Wilsey 1996).…”
Section: Introductionmentioning
confidence: 99%